2014
DOI: 10.1371/journal.pone.0106738
|View full text |Cite
|
Sign up to set email alerts
|

Where There Is No Toilet: Water and Sanitation Environments of Domestic and Facility Births in Tanzania

Abstract: BackgroundInadequate water and sanitation during childbirth are likely to lead to poor maternal and newborn outcomes. This paper uses existing data sources to assess the water and sanitation (WATSAN) environment surrounding births in Tanzania in order to interrogate whether such estimates could be useful for guiding research, policy and monitoring initiatives.MethodsWe used the most recent Tanzania Demographic and Health Survey (DHS) to characterise the delivery location of births occurring between 2005 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
3
35
0
Order By: Relevance
“…25,26 Inadequate quality sanitation in HCF can also lead to embarrassment and discomfort in patients seeking medical assistance. In addition to the previously mentioned study which found that 44% of Tanzanian HCF performing deliveries were WATSAN-safe, 14 a 2014 assessment of Service Provision Assessment survey data from Ethiopia found that more than 26% of HCF across the country did not have a functioning latrine for patient use. 27 The previously mentioned Steinmann and others study of 12 HCF in India found that women consider sanitation and hand hygiene installations a vital part of HCFs; a lack of these amenities can detract from a facility's appeal and reputation, and can affect the consistency and timeliness of care seeking.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…25,26 Inadequate quality sanitation in HCF can also lead to embarrassment and discomfort in patients seeking medical assistance. In addition to the previously mentioned study which found that 44% of Tanzanian HCF performing deliveries were WATSAN-safe, 14 a 2014 assessment of Service Provision Assessment survey data from Ethiopia found that more than 26% of HCF across the country did not have a functioning latrine for patient use. 27 The previously mentioned Steinmann and others study of 12 HCF in India found that women consider sanitation and hand hygiene installations a vital part of HCFs; a lack of these amenities can detract from a facility's appeal and reputation, and can affect the consistency and timeliness of care seeking.…”
Section: Introductionmentioning
confidence: 83%
“…12 A 2014 qualitative study of 10 HCFs in a rural province in Cambodia documented suboptimal hand hygiene, unsafe water storage practices, and a lack of sanitation facilities in health centers where women give birth. 13 A 2011 study in Tanzania analyzed the Service Provision Assessment survey, documenting that 44% of health facilities that conduct deliveries have delivery rooms that are WATSAN-safe 14 ; a similar analysis of the Service Provision Assessment survey in Malawi revealed that 59.3% of HCF conducting deliveries had "safe, reliable, and accessible" water sources. 15 These studies are limited in scope and have focused on HCF in one country or a few HCF in one district or province.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review on association between poor sanitation and maternal mortality found that women of households with poor sanitation have 3.14 times higher odds of dying than women with better sanitation conditions. Further, women with poor water supply had 1.75 times odds of maternal mortality as compared to those with adequate water supply (Benova, 2014).…”
Section: Maternal Agementioning
confidence: 94%
“…20,21 For the case of Tanzania, 42.7% of its people rely on unsafe water sources for their domestic uses, only 36.8% have access to piped/tap water, 14% still practice open defecation, and 76.4% use traditional pit latrines. 22,23 Likewise, some people have to walk long distances to fetch water that may limit the amount of water available in the household for practicing good hygiene. The task of fetching water is the responsibility of women and children and may also affect time for mothers to feed and take care of the youngest children.…”
Section: Introductionmentioning
confidence: 99%